Combining InSAR and GPS to Determine Transient Movement and Thickness of a Seasonally Active Low‐Gradient Translational Landslide. Issue 3 (15th February 2018) - Hu, Xie; Lu, Zhong; Pierson, Thomas C.; Kramer, Rebecca; George, David L.
Abstract: The combined application of continuous Global Positioning System data (high temporal resolution) with spaceborne interferometric synthetic aperture radar data (high spatial resolution) can reveal much more about the complexity of large landslide movement than is possible with geodetic measurements tied to only a few specific measurement sites. This approach is applied to an 4 km 2 reactivated translational landslide in the Columbia River Gorge (Washington State), which moves mainly during the winter rainy season. Results reveal the complex three‐dimensional shape of the landslide mass, how onset of sliding relates to cumulative rainfall, how surface velocity during sliding varies with location on the topographically complex landslide surface, and how the ground surface subsides slightly in weeks prior to downslope sliding. Key Points: Sentinel‐1A InSAR and GPS results reveal rainfall‐triggered landslide‐body surface subsidence prior to downslope sliding 3D deformation measurements provide insights on the temporal and spatial complexity of landslide dynamics Spaceborne InSAR‐derived displacement fields can be used to invert for active landslide thickness variation based on mass conservation